Cyclothymic Disorder: A Cognitive Behavioral Case Formulation - Bertolucci, Ilaria (Journal of Psychology and Psychotherapy Research, 2024)
Cyclothymic disorder is recognized as a mild, less severe and subthreshold form of bipolar disorder. The complexity of the disorder leads to difficulties in diagnosis and treatment. A dimensional approach to diagnosis may help identify the goals, and the planning of the psychological intervention. In this paper, a case of cyclothymic disorder is presented, focusing on the cognitive-behavioral conceptualization of the case and its treatment planning.